2013
DOI: 10.1155/2013/579741
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of a Free Online HIV Treatment Response Prediction System for Reducing Virological Failures and Drug Costs after Antiretroviral Therapy Failure in a Resource-Limited Setting

Abstract: Objective. Antiretroviral drug selection in resource-limited settings is often dictated by strict protocols as part of a public health strategy. The objective of this retrospective study was to examine if the HIV-TRePS online treatment prediction tool could help reduce treatment failure and drug costs in such settings. Methods. The HIV-TRePS computational models were used to predict the probability of response to therapy for 206 cases of treatment change following failure in India. The models were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Indeed, a recent study of cases treated in India revealed that substantial cost savings may be possible through use of the system. 13 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study of cases treated in India revealed that substantial cost savings may be possible through use of the system. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The models described here are freely available online as part of the HIV Treatment Response Prediction System (HIV‐TRePS) which also enables physicians to model therapy costs. In a recent retrospective study using data from an Indian cohort, the system identified alternative, locally available regimens with a higher probability of response and lower annual costs than those prescribed in the clinic . The debate about the optimum allocation of resources to drugs, diagnostics and systems in such settings is an important one that is set to continue .…”
Section: Discussionmentioning
confidence: 99%
“…the clinic [10]. The debate about the optimum allocation of resources to drugs, diagnostics and systems in such settings is an important one that is set to continue [11].…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging the knowledge of a combination of all or some of these factors through rapid risk calculation to predict early viral outcomes in individual patients before initiation of ART would enhance clinical decision making and prevent adverse outcomes of treatment failure and the costs associated with switching to second line ART [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Attainment of early virological suppression depends on a number of factors including choice of initial ART regimen especially in ART naïve patients, ART adherence, comorbidities, and inter-individual variability in drug pharmacokinetics, demographic and genetic factors and drug resistance, baseline viral load and CD4 count [ 12 19 ]. Leveraging the knowledge of a combination of all or some of these factors through rapid risk calculation to predict early viral outcomes in individual patients before initiation of ART would enhance clinical decision making and prevent adverse outcomes of treatment failure and the costs associated with switching to second line ART [ 20 ].…”
Section: Introductionmentioning
confidence: 99%